Effect of Surgery of Endometrioma≥4 Cm on Fertility Rate and Pregnancy Outcome in women with infertility: A Randomized Clinical Trial - Fariba Seyedoshohadaei; Masoumeh Rezaie; Sholeh Shahgheibi; Nasrin Soufizadeh; Farnaz Zandvakili; Dayem Roshani; Maryam Ghorbanian (Mashhad University of Medical Sciences, 2020)
Introduction: Endometriosis is one of the most common chronic diseases in women that can cause infertility. Surgical removal of endometrioma can reduce pain and improve the quality of life of patients, while its effect on fertility is still controversial. This study was performed with aim to evaluate the effect of endometriosis surgery on fertility rate and outcomes in women with endometrioma.                                                Methods: This randomized controlled clinical trial was performed in 2017 on 64 women with endometrioma ≥ 4 cm. After random allocation, the intervention group received endometrioma surgery and the control group received expectant treatment. The two groups were followed for six months in terms of fertility. Data were collected using a researcher-made checklist. Data were analyzed by SPSS software (version 20) and independent t-test and Chi-square test. p < 0.05 was considered statistically significant                                                                     Results: Frequency of pregnancy in the intervention group (76.6%) was significantly different from the control group (46.6%) (p =0.023). Also, the frequency of spontaneous pregnancy was significantly different in the intervention and control groups (95.7%, N=22 vs. 42.9%, N=6) (P=0.001). Conclusion: Surgery of endometrium ≥4 cm is effective in infertile women and increases the chance of spontaneous pregnancy without other infertility treatments.